2016
DOI: 10.3389/fpls.2016.01011
|View full text |Cite
|
Sign up to set email alerts
|

Group 3 LEA Protein, ZmLEA3, Is Involved in Protection from Low Temperature Stress

Abstract: Late embryogenesis abundant (LEA) proteins are a family of small highly hydrophilic proteins that accumulate at the onset of seed desiccation and in response to adverse conditions such as drought, salinity, low temperature, or water deficit. In previous studies, we demonstrated that ZmLEA3 could enhance the transgenic tobacco tolerance to osmotic and oxidative stresses. Here, we demonstrated that the transcription of ZmLEA3 in the maize stems could be significantly induced by low temperature and osmotic stress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 32 publications
0
49
0
Order By: Relevance
“…In particular, CBF III and LEA group 3 clades are members of generic stress response gene families that are rapidly cold‐induced and that duplicated at the base of, and more locally within, Pooideae (this study; Sandve & Fjellheim, ; Li et al ., ; Liu et al ., ). Closely related paralogs in the CBF IV clade are cold‐inducible in the subtropical grasses rice (Ehrhartoideae; OsDREB1H , OsDREB1B and OsDREB1A ) and Cynodon dactylon (Chloridoideae) (Dubouzet et al ., ; Chen et al ., ), and the core Pooideae cereals wheat and barley (Badawi et al ., ; Stockinger et al ., ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In particular, CBF III and LEA group 3 clades are members of generic stress response gene families that are rapidly cold‐induced and that duplicated at the base of, and more locally within, Pooideae (this study; Sandve & Fjellheim, ; Li et al ., ; Liu et al ., ). Closely related paralogs in the CBF IV clade are cold‐inducible in the subtropical grasses rice (Ehrhartoideae; OsDREB1H , OsDREB1B and OsDREB1A ) and Cynodon dactylon (Chloridoideae) (Dubouzet et al ., ; Chen et al ., ), and the core Pooideae cereals wheat and barley (Badawi et al ., ; Stockinger et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Closely related paralogs in the CBF IV clade are cold‐inducible in the subtropical grasses rice (Ehrhartoideae; OsDREB1H , OsDREB1B and OsDREB1A ) and Cynodon dactylon (Chloridoideae) (Dubouzet et al ., ; Chen et al ., ), and the core Pooideae cereals wheat and barley (Badawi et al ., ; Stockinger et al ., ). Likewise, a LEA group 3 ortholog in the tropical grass maize is involved in low‐temperature responses (Liu et al ., ). These data collectively suggest functional diversification of CBF III and IV and LEA group 3 genes or differential partitioning of an ancestral cold‐responsive function following gene duplication and regulatory changes.…”
Section: Discussionmentioning
confidence: 97%
“…This protein is thought to be associated with stress tolerance in several plant species [137140]. Li et al .…”
Section: Discussionmentioning
confidence: 99%
“…BTF3 was previously reported to be involved in the transcription initiation by RNA polymerase II as well as in apoptosis. A recent study also demonstrated that silencing BTF3 expression in wheat through virus-induced gene silencing resulted in a more severe viral symptoms and reduced biomass (Liu et al 2016). LEA is known as a hydrophilic protein acting as a molecular chaperone to stabilize proteins, vesicles, and endomembrane (Gal et al 2004).…”
Section: Other Functional Groupsmentioning
confidence: 99%